2009
DOI: 10.1016/j.vetpar.2008.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterisation of Cryptosporidium and Giardia species in pre-weaned sheep in Australia

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. A c c e p t e d M a n u s c r i p t 2 AbstractA to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 25 publications
(40 reference statements)
7
91
1
5
Order By: Relevance
“…Xiao, 2010) but has not been detected in any human cryptosporidiosis cases in Australia to date. Quantification analysis using quantitative PCR (qPCR) and microscopy indicated that oocyst output in sheep feces varies widely and ranges from *1 to 10 6 oocysts per gramme (Yang et al 2009;Ryan et al, unpublished observations). Because sheep can harbour C. parvum, they should be considered a potential source of infection of Cryptosporidium either by direct transmission or by contamination of the environment.…”
Section: Sheepmentioning
confidence: 99%
“…Xiao, 2010) but has not been detected in any human cryptosporidiosis cases in Australia to date. Quantification analysis using quantitative PCR (qPCR) and microscopy indicated that oocyst output in sheep feces varies widely and ranges from *1 to 10 6 oocysts per gramme (Yang et al 2009;Ryan et al, unpublished observations). Because sheep can harbour C. parvum, they should be considered a potential source of infection of Cryptosporidium either by direct transmission or by contamination of the environment.…”
Section: Sheepmentioning
confidence: 99%
“…Cryptosporidium (including C. parvum) and Giardia were identified in all eight flocks included in the present study, and have been widely reported in sheep in Australia (Ryan et al, 2005;Yang et al, 2009;Sweeny et al, 2011;Sweeny et al, 2012a;Yang et al, 2014a;Yang et al, 2014b) and worldwide (Xiao 2010). Therefore the observations of reduced HSCW and dressing % associated with these organisms have important implications for sheep meat industries worldwide.…”
Section: Parvum (But Not All Cryptosporidium Spp)mentioning
confidence: 56%
“…An internal amplification control (IAC) which consisted of a fragment of a coding region from Jembrana Disease Virus cloned into a pGEM-T vector (Promega, USA), was used as previously described (Yang et al, 2013). All Cryptosporidium positives were screened using a C. parvum and C. hominis specific qPCR at a unique Cryptosporidium specific gene (Clec) that codes for a novel mucin-like glycoprotein that contains a C-type lectin domain (CTLD) previously described (Morgan et al, 1996;Yang et al, 2009;Bhalchandra et al, 2013). Cryptosporidium and Giardia oocysts per gram of faeces (g -1 ) were measured by qPCR as previously described (Yang et al, 2014a;2014b).…”
Section: Pcr Amplification -Cryptosporidium and Giardiamentioning
confidence: 99%
See 2 more Smart Citations